Marketing research with spss 10 cd - Burns, Alvin C.; Bush, Ronald F. ([S.l.] : Prentice Hall, 2001)
Undergrad text in Marketing research-Jr/Sr course. Only text to fully integrate SPSS. Upgraded to 10.0-CD included.